Development of Instrument For Academic Supervision The School Superintendents -Based CIPPO - Kaefahmi, Amhal; Supriyadi, Supriyadi; Wahyudin, Agus (Universitas Negeri Semarang, 2019)
Data from Education For All (EFA) Global Monitoring Report 2011: The Hidden Crisis, Armed conflict and Education issued by UNESCO March 1, 2011, Indonesia ranked 69th out of 127 countries with an education development index (EDI) index of 0.934. Data from The Learning Curve Pearson in 2014, the quality of Indonesian education ranks the last of the 40 countries surveyed. Similarly, the results of a survey conducted by the Organization for Economic Co-operation and Development (OECD), put Indonesia's quality of education in the order of 69 out of 76 countries surveyed. The low ranking of Indonesia in the field of education is the responsibility of all parties who are related, including the implementation of academic supervision of school supervisors that has not been maximized. The school supervisor's academic supervision instrument has not been developed as needed. The academic supervision instrument of the school supervisor in this study was developed using the CIPPO concept (context, input, process, product, and outcome) which is expected to produce an academic supervision instrument that effectively measures teacher performance. The objectives of this study were to: (1) describe and analyze academic supervision instruments (2) describe the development of CIPPO-based school supervisors / madrasah academic supervision instruments, and (3) test the validity, reliability, and practicality of Semarang-based Ministry of Religion supervisor's academic supervision instruments CIPPO. The research method used in this research is instrument development research. This study uses a research design development product performance instrument with nine steps, namely: (1) Determining Instrument Specifications with preliminary studies. (2) Writing Instruments. (3) Determining Scale. (4) Determining the Scoring System. (5) Reviewing instruments. (6) Assembling instruments. (7) Product testing & analysis. (8). Carry out Measurements, and (9), Analyze Final results. The steps are modified and divided into two important stages, namely: Preliminary Study Phase, and Development Study. Academic supervision instruments developed with CIPPO-based (hypothetical instruments) are carried out by evaluating instrument analysis assembled based on context, input, process, product, and outcome so that it fits the needs of teacher performance assessment in terms of preparation of RPP and implementation of teacher learning. And CIPPO-based school supervisors / madrasah academic supervision instruments are more effective than conventional academic supervision instruments